DEMYSTIFYING DOG BEHAVIOUR FOR THE VETERINARIAN - Shepherd, Kendal ([S.l.] : CRC PRESS, 2021)
The behaviour textbook that's been missing! - Dr Mandy Roshier, University of Nottingham, School of Veterinary Medicine and Science, UK This practical guide for busy veterinarians demystifies the apparently complex nature of canine behaviour while simultaneously emphasising its importance. Authored by acclaimed veterinary behaviour consultant Kendal Shepherd, the book provides practical knowledge of dog behaviour and an understanding of how to talk about it with clients. Shepherd shows how this can enhance the relationship between owner and pet and between dog and environment, including the vet surgery, as well as improve the vet's own sense of fulfilment and enjoyment of practice. From a discussion on the true nature of obedience to stressing the importance of behavioural indicators when assessing pain and mental welfare and finally by reminding vets of their obligations under Dangerous Dogs legislation, the emphasis is on the prevention of aggression throughout. Packed with anecdotes drawn from real-life cases, easy to read and understand, the principles explained can be effortlessly assimilated into the average consultation without the need for lengthy report-writing.
Foreword Introduction PART 1 -- Dogs and vets Chapter 1. What is a dog? Chapter 2. Do's and don't's of behaviourally aware general practice Chapter 3. 'Do as I do' Chapter 4. What is obedience? PART 2 -- Dogs and owners Chapter 5. The Ladder of Aggression Chapter 6. How to 'speak client' Chapter 7. Avoiding conflict i. Between dog and human ii. Between humans Chapter 8. The wisdom of children Chapter 9. The educational value of analogy Chapter 10. Walking a mile in a client's moccasins PART 3 -- Dogs and the law Chapter 11. Vets and the law Chapter 12. Legal cases to illustrate behavioural principles Overdependence on physical control Misunderstanding of obedience Significance of veterinary history Bad human behaviour Redirected aggression Misdirected play Conflict with police Chapter 13. The dilemma dogs face Post-script
OCLC-licensed vendor bibliographic record.
Keywords: Dogs -- Behavior; MEDICAL / Veterinary Medicine / Food Animal; PETS / Dogs / General